2009
DOI: 10.5021/ad.2009.21.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Features of Generalized Granuloma Annulare with Their Correlation: A Retrospective Multicenter Study in Korea

Abstract: Background: Generalized granuloma annulare (GGA) is a benign skin disorder of an unknown etiology. Though some cases of GGA have been reported, few systemic reviews of the clinical and pathological features of GGA have been performed. Objective: The purpose of this study is to analyze and correlate the clinical and pathological characteristics of GGA in Korean patients. Methods: We conducted a retrospective study that included 54 biopsy specimens of Korean GGA patients, and the clinical and pathological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 25 publications
4
73
1
10
Order By: Relevance
“…[6] In a study by Yun et al, 28 out of 54 patients showed necrobiotic collagen with classic palisading granulomas while interstitial pattern without much collagen alteration was seen in 26 patients. [7] We did not find significant vascular changes in our study. No vessel wall damage, fibrin thrombi or extravasation of RBCs was seen.…”
Section: Discussionmentioning
confidence: 52%
“…[6] In a study by Yun et al, 28 out of 54 patients showed necrobiotic collagen with classic palisading granulomas while interstitial pattern without much collagen alteration was seen in 26 patients. [7] We did not find significant vascular changes in our study. No vessel wall damage, fibrin thrombi or extravasation of RBCs was seen.…”
Section: Discussionmentioning
confidence: 52%
“…We report a case of clearance of GA with infliximab, with histological confirmation of the complete disappearance of granulomatous lesions. Granuloma annulare is a primarily idiopathic inflammatory condition sometimes associated with general diseases, most notably diabetes . Diffuse forms with functional, esthetic, and psychological impact often require treatment.…”
Section: Discussionmentioning
confidence: 99%
“…diyabetes mellitus ile ilişkisi, uzun süren seyri, spontan gerilemenin çok nadir görülmesi ve tedavilere yanıtının zayıf olması gibi farklı özellikleri bulunmaktadır 1,8 . Klinik olarak gövde ve ekstremite yerleşimli olan lezyonlar deri renginde, eritemli ya da viyolase renkli, sınırları hafif kabarık dermal papül ya da küçük anuler plaklar ile karakterizedir.…”
Section: Resim1unclassified
“…Klinik olarak gövde ve ekstremite yerleşimli olan lezyonlar deri renginde, eritemli ya da viyolase renkli, sınırları hafif kabarık dermal papül ya da küçük anuler plaklar ile karakterizedir. Histopatolojik olarak dermiste nekrobiyotik kollajeni çevreleyen histiyositler, lenfositler ve multinükleer dev hücreler saptanmaktadır 1,7 . Bizim olgumuza da benzer klinik ve histopatolojik bulgular eşliğinde dissemine GA tanısı konulmuştur.…”
Section: Resim1unclassified
See 1 more Smart Citation